DEVELOPMENT OF STUDENT WORKSHEETS SCIENCE PROCESS SKILLS BASED ON THE ACID-BASE MATERIAL - agung widodo; chansyanah diawati; nina kadaritna (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
Most of the concepts in chemistry are abstract. So the potential misconception that is common to the students, so it is necessary to develop the learning medium, especially in the student worksheet. This study aims to develop student works-heet based on science process skills. In this study, using the method of research and development (Research and Development) by Borg Gall and Gall, 1989 (Sukmadinata, 2009). Results of student worksheets developed are student worksheets that can measure students' science process skills. Furthermore performed limited testing to see what students and teachers based on student worksheets science process skills are developed. Limited testing done at one school in the town of Bandar Lampung. Based on limited testing for teachers on aspects of compliance content, readability, and the construction of the student worksheet based on science process skills obtained results respectively 90%, 85%, and 88.88%. While the limited testing conducted for the students to aspects kemenarikan, legibility and keterlaksanaan the student worksheet based on science process skills acquired respectively 88.93%, 87.85%, and 100%. Based on these results can be simpulankan the student worksheet based on science process skills can increase student interest and may assist students in the mastery of concept sespecially inacid-base material.Keywords: student worksheet, science process skills, acid-base.